HUBUNGAN KETERAMPILAN MEMBACA PEMAHAMAN BERITA DAN KETERAMPILAN MENULIS BERITA SISWA KELAS X SMK NEGERI 2 PAINAN - Yuni, Wirda; Thahar, Harris Effendi; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2016)
ABSTRACT The purpose of this study describe (1) the ability of reading news comprehension class X SMK Negeri 2 Painan, (2) the ability to write news class X students of SMK Negeri 2 Painan, (3) the relationship of reading news comprehension skills with the ability to write an news SMK Negeri 2 class X Painan. The data in this study were collected by using objective test and a performance test. The findings of the study (1) the ability of reading news comprehension class X students of SMK Negeri 2 Painan are in more than enough qualification (71,09), (2) the ability to write news class X students of SMK Negeri 2 Painan are more than enough to qualify (73,61), (3) there is a significant relationship between reading news comprehension skills with the ability to write news class X SMK Negeri 2 Painan. Kata kunci : membaca pemahaman berita, menulis berita